Graphene hybrid with Al₂O₃ base spent lubricants/eg (C₂H₆O₂) as nanolubri-coolants for machining Ti6Al4V material - Lim, Syh Kai (2024)
Lubricants usage for lubrication and cooling in the manufacturing engineering industry due to their pleasant attributes of good lubricity, high quality viscosity index and production desirable mechanical parts. However, failure of conventional lubricants at elevated temperatures and machining hard-to-process material such as Ti6Al4V, which exhibited poor thermal conductivity property and concentrated heat generation during machining process caused chip welding to accelerate insert wear. The performance limitation can be ameliorated by introducing hybrid nanoparticles to enhance the thermophysical and anti-wear properties of lubricants. The research aim to newly formulate hybrid nanolubri-coolants using graphene (G) and aluminium oxide (Al2O3) nanoparticles with the objectives to investigate the thermophysical and tribological properties as well as introducing the optimum hybrid ratio and concentration of nanolubri-coolant through minimum quantity cooling lubrication (MQCL) system in machining Ti6Al4V workpiece. Initially, the G-Al2O3 nanolubri-coolant was prepared at different composition ratio of 80:20, 60:40, 40:60 and 20:80 (ratio of G to Al2O3 in volume percent) for a constant 1.0% volume concentration. Next, the thermal conductivity, dynamic viscosity and density of nanolubri-coolants were measured using analytical laboratory equipment, whereas the kinematic viscosity and viscosity index (VI) were calculated by using mathematical equation and ASTM D2270 standard chart calculation. The tribological performance investigation was conducted in four-ball tribotester machine with specific circumstances according to ASTM D4172 standard. Results showed that among 4 composition ratios, the hybrid ratio of 60:40 was observed to be the most effective composition ratio according to the evaluation of thermophysical properties of thermal conductivity enhancement, dynamic viscosity enhancement, high value of VI and evaluation of tribological performances in terms of superior friction reduction, lower worn scar diameter and excellent surface quality. Furthermore, the G-Al2O3 hybrid nanolubri-coolant was prepared at different volume concentration from 0.5% to 1.5% for optimum composition ratio based on the outcomes of thermophysical and tribological properties evaluation and compared with the base lubricants. The turning experiments were performed using best concentration of G-Al2O3 hybrid nanolubri-coolants in MQCL system to evaluate the machinability performance of cutting Ti6Al4V. In the MQCL turning process, the hybrid nanolubri-coolants obtained maximum reduction of machining temperature by 31% and the cutting insert wear significantly reduced to 40.5%, minimize surface roughness as well as extended cutting insert life by 33.9%. Finally, it was recommended to formulate the G-Al2O3 hybrid nanolubri-coolants with hybrid ratio of 60:40 (60% G to 40% Al2O3) for application in machining of hard-to-cut material, Ti6Al4V workpiece due to this lubricant capable to formation of protective tribo-film and ball rolling mechanism effects as well as superior hybrid cooling lubrication that has been established in this research provided another alternative to the world dominating mineral oil based lubricants for more sustainable manufacturing environment.